Kunxian capsules in the treatment of patients with ankylosing spondylitis: a randomized placebo-controlled clinical trial. Issue 1 (December 2016) - Li, Qiuxia; Li, Li; Bi, Liqi; Xiao, Changhong; Lin, Zhiming; Cao, Shuangyan; Liao, Zetao; Gu, Jieruo
Abstract Background Ankylosing spondylitis (AS) is a chronic inflammatory autoimmune disease. Kunxian capsule, a Chinese patent medicine which has been used in the treatment of immunologic diseases for many years in China, has anti-inflammatory and immunoregulatory effects. This study investigates the efficacy and safety of Kunxian capsules in the treatment of AS. Method This was a randomized, double-blind, parallel control clinical trial involving 80 patients with AS who fulfilled the modified New York criteria (1984) and had active disease defined by a Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) ≥40 mm under background stable nonsteroidal anti-inflammatory drugs (NSAIDs) for more than 4 weeks. Patients were randomly divided into two groups, the Kunxian group and the placebo group, and Kunxian (0.6 g, three times per day) and the placebo were provided for 12 weeks. The primary endpoint was the Assessment of SpondyloArthritis international Society (ASAS) 20 response rate at week 12. The secondary endpoints were ASAS 40, BASDAI 50, the Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), and Ankylosing Spondylitis Disease Activity Score on the basis of C-reactive protein level (ASDAS-CRP) at weeks 2, 6, and 12. Results The primary endpoint of ASAS 20 at week 12 was achieved in 13 of 35 patients (37.1 %) among the Kunxian group, compared with 4 of 33 (12.1 %) in the placebo group (p  < 0.05). Significant improvement (BASDAI 50) was also observed between the Kunxian group and the placebo group at week 6 (14 (40 %) and 5 (15.5 %), respectively, p  < 0.05). At weeks 2, 6, and 12, the ASDAS-CRP level of the Kunxian group was significantly lower than that of the placebo group, especially at week 6 (p  < 0.01). Kunxian obviously reduced CRP levels compared to placebo at weeks 2, 6, and 12 (p  < 0.05). Compared with the placebo, Kunxian was associated with greater improvements in signs and symptoms of patients with AS from the baseline to week 12, and significant intergroup differences of additional composite indices of disease activity (i.e., erythrocyte sedimentation rate, patient global assessment of disease activity, total back pain, level of morning stiffness, tender joints, and BASFI scores) were also observed. Conclusion Kunxian capsule significantly decreased the disease activity of patients with AS. Trial registration NCT00953979 . Registered on 5 August 2009.